Access to Agricultural Extension Services and Their Influence on Crop Production among Rural Women Cooperative Farmers in South-East Nigeria (Nigerian Journal of Cooperative Economics and Management, 2026)
Agricultural extension service and its influence on crop production among rural women cooperative farmers in South-East, Nigeria is the focus of the study. Nigerian agricultural system has not been living up to expectation, despite the wide range of programmes, policies and approaches that have been formulated for enhancement and sustenance of agricultural growth. Importantly, women farmers are central to the success and hence their access to extension services has become key to boosting crop production. Towards addressing these issues the objectives of the study are to assess the level of use of agricultural extension services from point of access to technology, advisory services and facilitation by the rural women cooperative farmers and importantly, to determine if their access to these agricultural extension services have a significant effect on their crop production. Finally, the third objective identified factors that constrain the effective use of agricultural extension services by the rural women farmers. Taro Yamane (1967) formula and multistage sampling procedure were used in determining the sample size of 379 respondents after data sorting and ensuring representative distribution of samples to five states of Abia, Anambra, Ebonyi, Enugu and Imo in South-East, Nigeria. The study used descriptive and inferential statistics to analyse the data. The rural women cooperative farmers had grand mean for access to agricultural extension services: technology services (x=̄ 3.71); advisory services (x ̄ = 3.39); and, facilitation services (x=̄ 3.94). Thus, indicating that the women farmers had access to the three agricultural extension services components. The rural women grand mean for crop output (x=4.07)̄ , showed a positive production effect. Also, a t-ratio of 148.602 indicated that the use of agricultural extension service had a significant effect on crop output performance of the rural women cooperative farmers. However, the optimal realization of their extension access were hindered by some challenges such as poor infrastructure, low educational background, lack of credit, corruption and land acquisition.
Keywords: Agricultural Extension services; Crop production; Rural women farmers